2020
DOI: 10.1177/0194599820933183
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postoperative Radiation Following Laser Resection in Early‐Stage Glottic Cancer

Abstract: Objective Guideline recommendations for the treatment of early-stage glottic cancer are limited to single-modality therapy with surgery or radiation alone. We sought to investigate the clinicopathologic and treatment factors associated with the use of postoperative radiation therapy (PORT) following laser excision for patients with T1-T2N0 glottic squamous cell carcinoma (SCC). Study Design Retrospective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Cases treated at non-academic centers and those with lower caseloads had a higher likelihood of positive margins [ 21 ]. Silverman et al showed that postoperative radiotherapy of T1-T2 LSCC was significantly more common in low-volume centers [ 22 ]. In our study, positive margin status in T1a was associated with a higher risk of local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Cases treated at non-academic centers and those with lower caseloads had a higher likelihood of positive margins [ 21 ]. Silverman et al showed that postoperative radiotherapy of T1-T2 LSCC was significantly more common in low-volume centers [ 22 ]. In our study, positive margin status in T1a was associated with a higher risk of local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment decisions for re-operative procedures and adjuvant therapy draw from the results of margin evaluation among other pathologic factors. 1,[20][21][22] Patients who do not undergo margin evaluation may either not receive adequate treatment for their extent of disease, or conversely, may receive additional treatment that is unwarranted and associated with additional morbidity and complications. Furthermore, the present study found that surgical margins were more often evaluated after more radical endoscopic surgeries (86.9% for subtotal laryngectomies versus 51.8% for local excisions versus 33.1% for local destruction).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with patients who did not or could not have margins evaluated, who may receive adjuvant radiation due to the uncertainty of surgical margin status despite current guidelines recommending single‐modality therapy. Treatment decisions for re‐operative procedures and adjuvant therapy draw from the results of margin evaluation among other pathologic factors 1,20–22 . Patients who do not undergo margin evaluation may either not receive adequate treatment for their extent of disease, or conversely, may receive additional treatment that is unwarranted and associated with additional morbidity and complications.…”
Section: Discussionmentioning
confidence: 99%